ACTR-22. A PHASE I STUDY OF CYTOSINE DEAMINASE-EXPRESSING NEURAL STEM CELLS (CD-NSCs) ADMINISTERED INTRACRANIALLY AND IN COMBINATION WITH ORAL 5-FLUOROCYTOSINE (5-FC) AND LEUCOVORIN IN PATIENTS WITH RECURRENT HIGH GRADE GLIOMA. (5th November 2018) - Portnow, Jana; Synold, Timothy; Badie, Behnam; Blanchard, Suzette; Kilpatrick, Julie; Tirughana, Revathiswari; Metz, Marianne; Tran, Vivi; Aboody, Karen
Abstract: BACKGROUND: Human NSCs are tumor tropic, making them attractive vehicles for delivery of therapeutics. An immortalized, clonal NSC line was retrovirally transduced to express CD, which converts 5-FC to 5-fluorouracil (5-FU). The primary objectives of this study were to assess the feasibility of serially administering CD-NSCs intracranially via a Rickham catheter and determine the recommended doses for phase II testing (RP2D). METHODS: Adult patients with recurrent high grade gliomas underwent tumor resection or biopsy and placement of a Rickham. CD-NSCs were injected during surgery and thereafter infused through the Rickham every 2 weeks. Three days after each dose of CD-NSCs, patients took 5-FC (and leucovorin—dose level 3 patients only) orally every 6 hours for 7 days. The dose of CD-NSCs was escalated from 50 x 10 6 to 150 x 10 6 using a standard 3 + 3 design. 5-FC and leucovorin doses were 37.5 mg/kg and 25 mg, respectively. A treatment cycle was 28 days, with CD-NSCs administered on days 1 and 15, followed by 5-FC (and leucovorin) on days 4–10 and 18–24. Blood samples were drawn to assess for possible anti-NSC antibody and T cell responses. RESULTS: Fifteen evaluable patients received a median of 2 (range 1–5) cycles of study treatment. One dose-limiting toxicity occurred: grade 3 wound infection. Three patients developed anti-NSC antibodies after receiving 3 doses of NSCs. There was no correlation between these results and use of dexamethasone or number of cycles. Analyses of PK and possible anti-NSC T cell responses are ongoing. Three patients had stable disease for 5 months. CONCLUSIONS: Use of a Rickham to serially administer CD-NSCs intracranially is safe and feasible. Study treatment was well tolerated. There were no clinical signs of immunogenicity to these allogeneic CD-NSCs. The RP2D is 150 million CD-NSCs, 37.5 mg/kg of 5-FC, and 25 mg of leucovorin per dose.